Development and Evaluation of Novel Bionanoparticles Loaded with Nanosized Lamotrigine by Using the Novel Isolated Biopolymer from Phaseolus vulgaris Seeds (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The aim of this research was to isolate and characterize the novel biopolymer from Phaseolus vulgaris seeds and to formulate lamotrigine loaded bionanoparticles using this biomaterial. The biopolymer was isolated by simplified and economical process and analysed for different physico-chemical and spectral properties. The nanosizing of lamotrigine was done by bath sonication method and its particle size in nano-range was screened by UV method. The bionanosuspension loaded with nanosized lamotrigine was prepared by bath sonication for 15 cycles (1cycle equal to 3 minutes). The formulated bionanosuspension loaded with lamotrigine using biopolymer was compared with lamotrigine loaded bionanosuspension by using HPMC. The bionanosuspension was subjected for pH study, dispersibility study, % entrapment efficiency, nanosizing screening, particle size study and in vitro study for drug release and stability study of formulated bionanosuspension. The best formulation LPVu7 showed up to 90.36 ±0.9% drug release in 36 hours. having t 50% of 17 hours and t80% of 29 hours with r2 value of 0.9927 as compared to release from LSP5 with 92.43±0.68% having t 50% of 16 hours and t80% of 28 hours with r2 value of 0.9951 in 36 hours. The results reveal that isolated biopolymer may be used as an alternative to synthetic polymer because of its novel inbuilt bioretardant cum biostabilizing properties. The formulated bionanosuspension are feasible for delivering the nanosized lamotrigine in sustained manner for prolonged time for long term treatment of epilepsy.